Predicting - between the Need and Inability - Golka, Marian (Studia Oeconomica Posnaniensia, 2017)
The desire to predict the future probably has its source in the pursuit of the sense of security. The necessity of having ideas about the future manifests itself also nowadays. Such needs are felt by individuals, enterprises, cities, regions and states. Such knowledge is also needed in the world on a global scale: that otherwise is perhaps the most important, but also the most difficult to imagine. In the paper, general theoretical considerations are presented. First, attention is paid to the most important problems of the modern world, concerning which we should have more or less certain ideas about their manifestations in the near and more distant future. Next, various ways of prediction, including futurological forecasting and its methods will be recalled. The most important, however, is the question of the causes of failure of most forecasts and the disappointments they entail. Those are due, among other things, to the complexity of social life, the multiplicity of causative factors and the existence of probably unpredictable mental phenomena such as human attitudes, values and ideas.